The MIDWIFERY CARE MANAGEMENT FOR MRS. H, A 25-YEAR-OLD PRIMIGRAVIDA AT 9 WEEKS OF GESTATION WITH MORNING SICKNESS AT CITRA PRIMARY CLINIC IN 2026 - Titis Jernih Wati Gea; Sarispi; Nova Elisa; Mala Pianti Manik; Kismiasih Adethia; Nurlela Juniarti (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Morning sickness or nausea and vomiting of pregnancy (NVP) is a common physiological condition occurring in the first trimester due to hormonal changes, particularly increased levels of human chorionic gonadotropin (hCG), estrogen, and progesterone. Globally, approximately 50–80% of pregnant women experience nausea and vomiting with varying severity, which may affect maternal quality of life and nutritional status if not properly managed. Methods: This study used a descriptive case study design on Mrs. H, a 25-year-old G1P0A0 woman at 9 weeks of gestation at Pratama Citra Clinic in 2026. Data were collected through anamnesis, physical examination, and documentation using the Varney midwifery management approach Results: The patient experienced mild nausea and vomiting, especially in the morning, without signs of dehydration and with normal vital signs, indicating physiological morning sickness. The care provided included education about pregnancy conditions, recommendations for small frequent meals, adequate fluid intake, and emotional support from the family.Conclusions: Morning sickness in this case is a physiological condition that can be effectively managed through comprehensive midwifery care based on education and non-pharmacological approaches to prevent complications. Keywords: Morning sickness, first trimester pregnancy, midwifery care, nausea and vomiting.